Pahrudin, Trisno Martono, Wiedy PENGARUH KOMPETENSI PEDAGOGIK, KEPRIBADIAN, PROFESIONAL DAN KOMPETENSI SOSIAL GURU TERHADAP HASIL BELAJAR EKONOMI SISWA SMA NEGERI DI KABUPATEN LOMBOK TIMUR TAHUN PELAJARAN 2015/2016 - Pahrudin, Pahrudin (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT The purpose of this study are: 1) To determine the effect of direct pedagogical, personal, professional and social economics teachers to the learning outcomes of students in high schools in East Lombok district in the academic year 2015/2016. 2) To determine the effect of indirect pedagogical, personality and social skills through professional competence of teachers on student learning outcomes SMA economy in East Lombok district in the academic year 2015/2016. This study is a descriptive survey denganjenis. This study uses a study population with the number 32 economics teachers in high schools in East Lombok. The data in this study were collected through questionnaires and documentation, and then analyzed using path analysis (path analysis) using SPSS Vesi 19 Results showed that the pedagogical competence of teachers direct positive effect on learning outcomes economy by 18.7%, personal competence directly influence the results of the economic study was 26%, the professional competence of teachers directly influence student learning outcomes by 30.8%, social competence of teachers direct effect on student learning outcomes by 28.8%, pedagogical competence indirect effect on student learning outcomes through professional competence of 0.074, personal competence indirect effect on student learning outcomes through professional competence of 0.082, and social competence indirect effect on results student learning through professional competence of 0.158. Key words: Student Learning Outcomes Economics, Pedagogical Competence, Competence Personality, Professional Competence, Social Competence